Answer:
for k = 0, 1, 2
=
( cos(90 + k*120) + i sin (90 + k*120) )
Choice: C. for k = 1
=
( cos(210) + i sin (210) )
Explanation:
Rewrite -2i as 2*( 0 - i) = 2 * (sin π + i*cos π)
(-2i)^(1/3) = [2 (cos 3π/2 + i sin 3π/2) ]^(1/3)
(-2i)^(1/3) = 2^(1/3) (cos 3π/2 + i sin 3π/2)^(1/3)
(-2i)^(1/3) = 2^(1/3) ( cos ((3π/2 + 2kπ)/3 ) + i sin ((3π/2 + 2kπ)/3 ) )
for k = 0, 1, 2
=
( cos (π/2 + 2kπ/3) + i sin (π/2 + 2kπ/3) )
for k = 0, 1, 2
=
( cos(90 + k*120) + i sin (90 + k*120) )
for k = 0, 1, 2
so we can let k = 0 and get:
=
( cos(90) + i sin (90) )
for k = 1
=
( cos(90 + 120) + i sin (90 + 120) )
=
( cos(210) + i sin (210) )